2021
DOI: 10.1136/bmjopen-2020-043554
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking behaviours among older adults: a scoping review protocol

Abstract: IntroductionDespite evidence that illustrates the unmet healthcare needs of older adults, there is limited research examining their help-seeking behaviour, of which direct intervention can improve patient outcomes. Research in this area conducted with a focus on ethnic minority older adults is also needed, as their help-seeking behaviours may be influenced by various cultural factors. This scoping review aims to explore the global literature on the factors associated with help-seeking behaviours of older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This scoping review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines (Tricco et al, 2018; Supplementary File 1) and is registered with the Open Science Framework (Teo, 2020). Further methodological details, additional definitions, and the published protocol for this scoping review are available online (Teo et al, 2021). The methods were also informed by Arksey and O’Malley (2005), which are described below.…”
Section: Methodsmentioning
confidence: 99%
“…This scoping review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines (Tricco et al, 2018; Supplementary File 1) and is registered with the Open Science Framework (Teo, 2020). Further methodological details, additional definitions, and the published protocol for this scoping review are available online (Teo et al, 2021). The methods were also informed by Arksey and O’Malley (2005), which are described below.…”
Section: Methodsmentioning
confidence: 99%
“…Older persons, for example, have been found to have a higher level of consciousness and awareness, a greater sense of responsibility for their health and, inevitably, a greater level of concern regarding their health. However, a recent scoping review of 52 studies on the health‐seeking behaviours of older adults showed contrasting findings; that older adults often failed to ask for help when ill (Teo et al., 2021). In addition, the review reported that older adults would commonly self‐assess their health first to determine whether seeking help was necessary; they often indicated that health‐seeking was viewed as a threat to their independence.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with greater knowledge are more likely to maintain control over their condition than those without reliable health information. Moreover, well‐informed individuals are better suited to deal with the uncertainty of disease and the necessary treatments (Teo et al., 2021). Although health information is insufficient to motivate behaviour modification, it is essential and foundational to healthcare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care-seeking behaviour: involves finding solutions to a health challenge [ 14 ]. Knowledge of care-seeking options and actual care-seeking have been recently investigated with support for improving information about care options [ 15 ].…”
Section: Introductionmentioning
confidence: 99%